Female Gender and Resistance to Activated Protein C (FV:Q506) as Potential Risk Factors for Thrombosis after Elective Hip Arthroplasty - Svensson, P J; Benoni, G; Fredin, H; Bjӧrgell, O; Nilsson, P; Hedlund, U; Nylander, G; Bergqvist, D; Dahlbäck, B (Thrombosis and Haemostasis, 1997)
Resistance to activated protein C (APC) caused by the R506Q mutation in factor V is the most common inherited risk factor for venous thrombosis. To elucidate whether APC-resistance is a risk factor for venous thrombosis after elective total hip replacement, the association between APC-resistance (presence of FV:Q506 allele) and postoperative thrombosis was investigated in patients (n = 198) randomised to received short (during hospitalisation, n = 100) or prolonged prophylaxis (three weeks after hospitalisation, n = 98) with low molecular weight heparin (LMWH). Among APC-resistant individuals receiving short prophylaxis, 7/10 developed thrombosis as compared to 2/12 receiving long prophylaxis (p <0.0179). Odds ratio for association between APC-resistance and thrombosis in the short prophylaxis group was 4.2 (CI 95% 1.02-17.5) (p <0.0465). Among those receiving prolonged, prophylaxis, there was no increased incidence of thrombosis associated with APC-resistance. Two unexpected observations were made. One was that APC-resistance was much more common in women (19/109) than in men (3/89) (p <0.001). The other was that even women without APC-resistance were much more thrombosis-prone than men. Thus, 24/48 of women with normal FV genotype and short prophylaxis developed thrombosis vs 8/42 among men, p = 0.002. The increased risk of thrombosis associated with female gender and APC-resistance was neutralised by the prolonged treatment. In conclusion, among patients receiving short prophylaxis, female gender was found to be a strong risk factor for venous thrombosis. Even though APC-resistance appeared to be a risk factor for postoperative thrombosis, the uneven distribution of APC-resistance between men and women, taken together with the increased risk of thrombosis among women, precluded valid conclusions to be drawn about the association between APC-resistance and an increased risk of thrombosis. Our results suggest that prolonged prophylaxis with LMWH after hip surgery is more important for women than for men.